A segunda independência. Emancipadores, abolicionistas e as emancipações do Brasil - BEZERRA NETO, José Maia (Universidade Federal do Pará, 2017)
This article analyses the emancipationist and abolitionist representations against slavery and its associations with the Brazilian history and memory of the Independence. This image was built as patriotic and as an expression of the national will, which, according to emancipationists and abolitionists, concluded the process of Independence. It focuses on the selection of specific events related to the emancipation of slaves.